Analisis Misalignment Pada Unit High Pressure Fluidized Bad Menggunakan Dial Indicator - Suherna, Suherna; Kelana, Nikho Bayu Kusuma; Nurdin, Akhmad (Program Studi Kesehatan dan Keselamatan Kerja, 2022)
Rotation machines are one of the driving machines that are widely used in industrial factories because they are strong, reliable, easy to maintain and efficient. Installation of the machine with other equipment requires accuracy so that the axis between the two is truly an axis of